Combination of the Spritz Algorithm and the Bit Plane Complexity Segmentation Technique in Text Security - Yusdartono, Dessy Yusvika; Yusdartono, Habib Muharry (Bahasa Indonesia, 2024)
Communication is the primary needs of the daily life. As human, communication is important. Through communication, some process of the message is exchanged between the sender and the recipient. The rapid advancement of information technology make security has become an important aspect of the communication, especially when it involves confidential messages. The presence of cryptography has proven to secure these secret messages by encrypting them into a form that cannot be easily understood. Additionally, the technique of steganography allows secret messages to be embedded into digital image, thereby enhancing the security of these messages. The Spritz Algorithm and Bit Plane Complexity Segmentation (BPCS) Technique are the methods of cryptography and steganography that can secure the secret messages, with the  embedding message capacity is 20% up to 60% of the cover media’s size. The results of these combination  are represented in a table that includes the plaintext, key length, ciphertext, and the size of the generated stego image.